Pengaruh Pelayanan Fiskus terhadap Kepatuhan Pajak Kendaraan Bermotor: Studi Empiris di Desa Sukanagara - Astuti, Dewi Ratnasari; Ridwan, Rizky; Prayoga, Cepi Juniar; Isnawati, Isnawati (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
This study was conducted with the objective of empirically testing and verifying the impact of the quality of service provided by fiscal authorities on motor vehicle tax compliance in Sukanagara Village. Motor vehicle taxpayers in this village, active in the fiscal year 2023, were used as the population for the study. A quantitative method was employed, where data was collected through questionnaires distributed to respondents and through literature review including academic journals and online sources. Several techniques were used to analyze the collected data. This included data quality tests to ensure the reliability of the data used, classical assumption tests to check the prerequisites for statistical analysis, and hypothesis testing to determine the significance of the impact of service quality on tax compliance. The results of this study are highly significant; based on the partial regression coefficient test or t-test, a t-value of 8.588 was obtained with a very low significance level (0.000), indicating a strong positive influence of the quality of fiscal services on motor vehicle tax compliance in Sukanagara Village. This shows that improvements in fiscal service quality have a direct impact on enhancing tax compliance among taxpayers, affirming the importance of high-quality services in improving the effectiveness of tax revenue collection. Keywords: Quality Of Service, Taxpayer Compliance